THE EFFECT OF DEFERRED TAX EXPENSE, CAPITAL INTENSITY AND FIRM SIZE ON TAX AGGRESSIVENESS (Case Study on BUMN20 IDX Company for the 2019-2021 Period) - Meylina Meylina; Moody Manalu (Faculty of Economic and Business Universitas STIKUBANK, 2022)
The research conducted by the author is to determine the effect of deferred tax on capital intensity, capital intensity, and firm size on tax aggressiveness. The sample used in this study is BEI BUMN20 (top twenty constituents) contained in the BEI BUMN20 Fact Sheet Index as of December 2022 during 2019-2022. The technique used is descriptive statistical analysis, classical assumption test, multiple linear regression test, and a test of the coefficient of determination. The test results show that the level of the deferred tax burden can have a positive but not significant effect on tax aggressiveness. Capital intensity has a significant effect on tax aggressiveness then company size has a positive but not significant effect on the tax aggressiveness variable. This variable depends on tax aggressiveness. The coefficient of determination obtained is 13.5%, which can be interpreted if the independent effect on the variable is 13.5%.